The nourished kitchen : farm-to-table recipes for the traditional foods lifestyle : featuring bone broths, fermented vegetables, grass-fed meats, wholesome fats, raw dairy, and kombuchas - McGruther, Jennifer (Ten Speed Press, 2014)
"A cookbook from the author of the popular website Nourished Kitchen, featuring 175 recipes based on the 'traditional foods' philosophy of eating, which emphasizes whole grains, dairy, red meat, organ meats, and fermented foods. A traditional foods diet celebrates unrefined, whole, and natural foods while avoiding modern, refined ones; it also seeks to prepare them in the same manner as our ancestors, prior to the industrialization of food. The traditional foods diet, based on the findings of Dr. Weston A. Price's anthropological data from the 1930s, suggests that cultures who subsist on native, unrefined, traditionally-prepared foods enjoy better health (with lower rates of infertility, heart disease, diabetes, and autoimmune disease) than those who consume a diet of processed foods. This cookbook offers a beautifully illustrated treatment of this nutrient-dense cooking style, with wholesome time-tested recipes including restorative bone broths, revitalizing kombuchas and tonics, and hearty and economical bean and lentil dishes. Contrary to nearly all of today's trendy diets, the traditional foods diet is not a restrictive eating style--it focuses on eating diversely and seasonally. It is more inclusive than the paleo diet and shares the environmental and ethical principles of the farm-to-table movement. Practical sidebars include tutorials on infusing honey, making homemade almond flour, preparing a sourdough starter, and rendering poultry fat. Beyond recipes, The Nourished Kitchen also addresses the larger issues of how modern convenience food bypasses traditional culinary wisdom and the critical importance of how food is sourced and prepared for optimal nutrition"--